How do Hofstede's cultural dimensions influence behaviour on crypto markets - Kučera, Tomáš; Jedlinský, Jakub; Bolotov, Ilya; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis investigates how national cultural characteristics, as defined by Hofstede’s cultural dimensions, influence cryptocurrency ownership rates across countries. Cryptocurrencies are a universally accessible financial tool, however, adoption patterns vary globally, generating questions about the role of culture in shaping cryptocurrency ownership. To discover the potential connection, the thesis builds on data from the Triple-A platform and Hofstede’s six cultural dimensions - Power Distance Index (PDI), Uncertainty Avoidance Index (UAI), Motivation Towards Achievement and Success (MTAS), Individualism versus Collectivism (IDV), Long-Term versus Short-Term Orientation (LTO), and Indulgence versus Restraint (IND) - and applies correlational, regression, and comparative analyses to a sample of over 100 countries. The findings reveal that Motivation Towards Achievement and Success (MTAS) is the only cultural dimension showing a consistent and statistically most significant positive correlation with cryptocurrency ownership. These results highlight the limited but existing influence of culture on cryptocurrency market behaviour and suggest that culturally driven motivations related to ambition, competitiveness, and financial success play a role in shaping cryptocurrency ownership.
Vedoucí práce: Jakub Jedlinský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses